2003
DOI: 10.1021/jp021790x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach for Measuring Absolute Rate Constants by Pulsed Electron Spin Resonance:  Addition of Phosphinoyl and 2-Hydroxy-2-propyl Radicals to Several Alkenes,

Abstract: A time-resolved Fourier transform electron spin resonance (TR FT ESR) method for determining absolute rate constants of reactive, free radical reactions is described. The phase memory times T M of a family of reacting radicals were measured precisely by electron spin-echo (ESE) detection. In all cases the ESE signal decays show a simple pseudo-first-order behavior. Rate constants of the reactions were extracted from the linear relationship between the reciprocal of the T M values and the alkene concentrations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 98 publications
3
26
0
Order By: Relevance
“…The procedures employed were based on the method reported by Weber and Turro. 34 The phase memory time, T M *, of a target radical was measured by the EPR apparatus under pulsed-microwave operation as follows. Electron spin echo (ESE) of the target radical was generated by a two-pulse sequence initiated at t ns after the laser flash (laser flash − t − π/2 − τ − π − τ − echo).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The procedures employed were based on the method reported by Weber and Turro. 34 The phase memory time, T M *, of a target radical was measured by the EPR apparatus under pulsed-microwave operation as follows. Electron spin echo (ESE) of the target radical was generated by a two-pulse sequence initiated at t ns after the laser flash (laser flash − t − π/2 − τ − π − τ − echo).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…10,31−33 Moreover, Weber and Turro reported that a pulsed EPR technique enables us to determine rate constants of addition reactions between initiator radicals and monomers. 34 In their procedures, the rate constants were determined by analyzing the linear relationship between monomer concentration and phase memory time of the reacting radical, the latter of which can be measured with high precision by the electron spin−echo detection method. 34 In the present study, the mechanisms for addition reactions of initiator radicals to various monomers were studied by the pulsed EPR spectroscopic method along with quantum chemical calculations for enthalpy and polar effects.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photo‐polymerization is described by the following schemes, R · + Mon k1 R‐(Mon) 1 · (the first step) R‐(Mon) 1 · + Mon k2 R‐(Mon) 2 · (the second step) R‐(Mon) n − 1 · + Mon kn R‐(Mon) n · (chain growth) and the early stage focused here is the first and the second steps. The rate constant k 1 for initiator radical R · at the first step were determined by using various spectroscopic methods such as photo‐acoustic spectroscopy, EPR, and transient absorption method . However, as for the time‐resolved spectroscopic study on the rate constant k 2 for the second step, there is no literature to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…The T M * can be measured with high precision through the two‐pulse electron spin echo (ESE) technique and therefore, k value can be determined from monomer concentration dependence of T M * −1 . This method has been applied to determine rate constants for addition reactions between initiator radicals and some monomers …”
Section: Introductionmentioning
confidence: 99%